Effect of Payment Gateway, Financial Literacy, Financial In - Dhiya Auliana (Universitas Udayana, 2024)
This study examines small and medium-sized enterprises (SMEs) in Mataram City'screative economy sector to ascertain the effect of payment gateways and financial literacyon SME performance with financial inclusion as an intervention variable. Research designthat is quantitative and descriptive is used in this study. Participants in this study weresmall and medium-sized enterprises (SMEs) from the creative economy who usepayment gateways. The sample included a total of fifty participants. The study's samplestrategy, known as snowball sampling, was utilized since it was unknown how manySMEs in the creative economy sector used payment gateways. The data source for theprimary information will be SMEs themselves. The results of the study show thatfinancial literacy and payment gateways have a considerable beneficial influence on SMEperformance. They also demonstrate that financial literacy and payment gateways havea significant positive impact on financial inclusion. However, neither financial inclusionas a standalone variable nor as an intervening factor had any effect on SME success.